(untitled) (Indian Journal of Animal Production and Management, 2013)
An investigation was undertaken to study the effect of season, parity, type of birth and teat abnormality on milk yield of local goats of Rohilkhand region. A total of 32 does were selected for the experiment, and were grouped according to season (rainy and winter), parity (primiparous and multiparous), type of birth (single and twin), and type of teat abnormality (normal teat and abnormal teat). All does were milked twice daily and milk yield was recorded up to 90 days. It was found that average daily milk yield (ADMY) and total milk yield of 90 days (TMY) were significantly (P<0.01) higher in rainy season (0.726±0.05 L ; 65.32±8.81 L) than winter season (0.657±0.02 L ; 57.91±3.51 L). Regarding parity, ADMY and TMY were significantly higher (P<0.01) in multiparous does (0.754±0.02 L and 66.76±3.97 L) than primiparous does (0.515±0.03 L and 45.73±3.18 L). Average TMY for single kidded and twin kidded does were 51.37±4.05 L and 65.89±4.53 L, respectively and it didn’t differ significantly. Presence of supernumerary teat (16%) was the prominent form of abnormality observed followed by bifurcal teats (4%) and asymmetrical udder (4%). Average milk production in does with teat abnormality was non-significantly lower than the normal animals. It can be concluded that milk production vary significantly with the season and parity in these local goats.